Retail regulation in South Korea: The NoBrand case - Jiyoon Cha; Yeonsoo Cho; Youngjin Yoon; Seungho Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This study examines how NoBrand has faced legal regulations in Korea, and NoBrand's transition to the franchise system to respond to regulatory changes (examined with a case analysis). In 2015, Emart, a Korean retail giant, launched its private brand (PB), NoBrand, to address stagnant sales. With advantages in price and quality due to supply chain management (SCM), NoBrand not only established a successful foothold, but also gained success in the market. Despite the rapid growth of NoBrand, it has faced government regulations that restrict its operations. To respond to these regulations, NoBrand changed its direct operating system to a franchise system that allows an individual owner to run his or her own NoBrand store. However, the transition triggered conflicts with both local stakeholders and other branches of its parent firm, Emart. By analyzing these conflicts, this study finds that Korean retail policy did not effectively protect small business owners as primarily aimed.
Keywords: 650; case study; franchise system; NoBrand; regulation; retail; retail policy